MERANCANG DAN IMPLEMENTASI VPN PPTP UNTUK KONEKSI CLIENT SERVER APLIKASI KEUANGAN IFAS (Studi Kasus Pada Yayasan Teratai Putih Global) - Masroni Masroni; Atit Pertiwi; Amat Suroso (Politeknik Harapan Bersama, 2021)
The Teratai Putih Global Foundation is an institution engaged in the field of education which has 9 (nine) school units from Islamic preschool, Islamic Elementary School, Islamic Junior High School, Islamic High School and Vocational Schools spread across Bekasi and Jakarta. The data collection process is mainly related to the administrative and financial processes of students and the recording of school financial cash flows. The foundation and the nine units have school administration system software IFAS (Integrated Finance and Accounting System) in their respective school units, this condition makes it difficult for the foundation to consolidate data and daily reports in real time because they are not connected to each other. VPN (Virtual Private Network) technology allows anyone to be able to access the local network from outside using the internet. The purpose of using a VPN is so that users can access the resources on the server, connect to the database server in real time and get the same rights and settings as physically in the place where the local network is located. With the NDLC (Network Development Life Cycle) method, a method for designing and building networks, VPN connections are designed for a client-server topology and successfully implemented for the IFAS program to run well and smoothly.